Cancer associated thrombosis in pediatric patients. Issue 1 (March 2022) - Barg, Assaf Arie; Kenet, Gili
Abstract: The etiology of pediatric cancer associated thrombosis (CAT) is multifactorial and may reflect pro-coagulant alterations of the hemostatic system induced by presence of cancer itself or by therapeutic chemotherapy, tumor mass effects, tumor thrombi, and inherited thrombophilia. Age, diagnosis of hematological malignancy and presence of a central venous line significantly increase the risk of thrombosis. With over 80% cure rates of childhood cancer, strategies for prevention as well as for early diagnosis and optimal treatment of (thromboembolism) TE in children with malignancies are of major importance. Currently use of therapeutic low molecular heparin (LMWH) still prevails, as prospective studies and real world data regarding Direct oral anticoagulant (DOAC) use for treatment or prevention of pediatric CAT are scarce. The following review will address the epidemiology, etiology and risk factors for CAT in children, and describe the presently available evidence associated with anticoagulant therapy and prevention strategies.